No farmer left behind in sustainable biofuel production - Lee, J.S.H.; Rist, L.; Obidzinski, K.; Ghazoul, J.; Koh, L.P. (2011)
Societal concerns about the social and environmental impacts of biofuel production are driving producers to adopt better management practices. Existing certification schemes for sustainable biofuel production are, however, biased towards industrial-scale producers that have the financial capital and economies of scale to meet sustainability and certification objectives. Smallholder farmers in developing countries, by contrast, often lack the means and capacity to do so. Some of the challenges faced by smallholders include high certification costs, insufficient institutional capacity, inadequate financial and social incentives, poor group organization and lack of external support. Drawing lessons from existing certification programs, we argue that proponents of sustainable practices and standards must fully appreciate the complex realities of smallholder production systems. We provide policy recommendations for ensuring that no farmer is left behind in the quest to increase sustainable biofuel production.